PENGARUH PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN MENGGUNAKAN LKS TERHADAP HASIL BELAJAR KIMIA PADA POKOK BAHASAN HIDROKARBON - Wesly Hutabarat; Ribka Septiani Napitupulu (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2015)
Abstract This research is intended to find out effect of cooperative learning Jigsawand worksheets for chemistry toward student learning outcomes at grade 10  SMANegeri 1 Silahisabungan is better than conventional teaching by using worksheets.The population in this study were all students in grade 11 SMA Negeri 1Silahisabungan which consists of three classes. The samples used in this study weretwo classes taken with purposive sampling technique. Instruments used to collectdata required consisted of 20 questions instruments that have previously been testedits validity, reliability and level of difficulty. The average value of learning outcomesand gain for the experimental class students was 79.83 and 0.705 respectively,meanwhile the average value of learning outcomes for students and gain controlclass are 75.17 and 0.626 respectively. Based on the data analyzed, it was  obtainedthat  tcalc. was 2.362 and ttable value was 1.6723 at a significance level of α = 0.05 anddf = 58, so that tcalc.> ttable. The percentage increase of student learning outcomes onthe experimental class and control class were 70.50% and 62.60%. It can beconcluded that the results of studying chemistry students who are taught withCooperative Learning Jigsaw type using worksheets was better than the results ofstudying chemistry students who are taught by conventional learning by usingworksheets on the subject of hydrocarbons in grade 10thth in SMA Negeri 1Silahisabungan year 2014/2015.thKata kunci:Gain, hidrokarbon, Jigsaw, and cooperatif.